Incidence and Risk Factors of Acute Kidney Failure in Patients Receiving Colistin in a Provincial Hospital - Taejaroenkul, Piyatida; Khamlek, Sunisa; Khienprasit, Nitta; Lucksiri, Aroonrut (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 1 (2019): January - March 2019, 2019)
The objectives of this study were to determine incidence and risk factors associated with acute kidney failure in patients receiving colistin. This study was a retrospective cohort study from medical records of patients who received colistin at Nakornping Hospital, Chiang Mai, during January 1, 2011 to December 31, 2013. The statistical analyses include descriptive statistic, multivariate analysis and Kaplan-Meier method.  The results showed that most patients were male (65.7%) with the median age of 67 years (range of 19-95 years). The median value of serum creatinine was 0.9 mg/dl (range of 0.3-6.7 mg/dl). Approximately half of the patients (50.7%) received loading doses and 46% (171 pateints) of them received colistin more than 5 mg/kg/day. The study observed 262 patients (70.8%) developed nephrotoxicity with the median onset of 7 days (95% CI 6-7). Among the patients who experienced nephrotoxicity, the severity of acute kidney failure of 101 cases (27.3 %) were classified as “failure”, 95 cases (25.7%) were classified as “risk” and 66 cases (17.8%) were classified as “injury”.  Multivariable analysis revealed the risk factors associated with acute kidney failure as follows: (1) age older than 70 years old (OR = 4.0; p = 0.001), (2) having diseases that may decrease renal blood flow (OR. = 2.1; p = 0.008), (3) receiving colistin more than 5 mg/kg/day (OR = 2.1; p = 0.007), and (4) co-administration of nephrotoxic drugs or drug affecting the glomuerulus filtration rate (OR = 1.8; p = 0.023).  However, the patients with baseline serum creatinine more than 1.2 mg/dl appeared to have lower risk of acute kidney failure than the patients with the values of serum creatinine less than or equal to 1.2 mg/dl. This study showed high incidence (70.8%) of acute kidney failure in patients receiving colistin.  Thus, renal functions should be closely monitored, especially in elderly patients, patients with diseases that may decrease renal blood flow, patients concurrently received nephrotoxic drugs or drug affecting the glomerular filtration rate. Besides, the patients’ weight should be used to determine the appropriate colistin dose and adjusting dose should be performed based on the pateints’ renal functions or avoiding the use of colistin doses greater than 5 mg/kg/day.   Keywords: colistin, acute kidney failure, nephrotoxicity